Consolidation and swelling behavior of kaolinite clay containing xanthan gum biopolymer - Kwon, Yeong Man; Chang, Ilhan; Cho, Gye Chun (Acta Geotechnica, 2023)
Recently, microbial biopolymer-based soil treatment (BPST) has gained attention for its application in environmentally friendly soil stabilization, particularly for enhancing the strength and stability of fine-grained soils. However, the effects of BPST on clay’s compressibility (consolidation) and expansion (swelling) behaviors remain unclear. This study used xanthan gum, a microbially produced polysaccharide with anionic charges, to stabilize kaolinite clay. The effect of xanthan gum BPST on the consolidation and swelling behavior of cohesive kaolinite clays was assessed through a series of experimental tests, including one-dimensional consolidation tests with elastic wave measurements, swelling tests, environmental scanning electron microscopy, and unconsolidated-undrained triaxial tests. The formation of xanthan gum hydrogels induces pore-clogging, resulting in a delay in the consolidation process, increased energy dissipation, and compressibility. Furthermore, the interaction between kaolinite and xanthan gum improved the undrained shear strength of kaolinite soils, thereby reducing the consolidation time required for a specific bearing capacity. This study demonstrates the possible application of controlling hydraulic conductivity, seismic stabilization, and rapid surface stabilization. However, additional drainage is necessary for in situ applications.
Keywords: Consolidation; Elastic wave; Kaolinite; Swelling; Xanthan gum biopolymer